Sistem Informasi Absensi Pegawai Kantor Desa Berbasis Web (Studi Kasus: Kantor Desa Way Lunik Kecamatan Abung Selatan) - Tri Suranti; M. Abu Jihad Plaza R (Jurnal Sains Informatika Terapan, 2026)
This research is motivated by the manual process of employee attendance recording at the Way Lunik Village Office, South Abung District, which is often time-consuming, prone to errors, and vulnerable to data manipulation. Therefore, the primary objective of this study is to design and implement a Web-Based Employee Attendance Information System as a digital solution to overcome these challenges. The design and development of this system adopt the Waterfall method. This method was chosen due to its linear and structured approach, starting from the stages of system and user requirements analysis, interface and database design, coding (implementation), and thorough system testing. The developed information system focuses on providing features for online clock-in and clock-out, managing employee data, and automating report generation. The results of the system implementation show a significant increase in administrative efficiency. The web-based system is capable of presenting attendance data accurately and in real-time, which was previously difficult to achieve with manual methods. The presence of digital features also successfully minimizes the potential for fraud and recording errors. Furthermore, the system provides structured daily, monthly, and performance recapitulation reports that are fast and readily available for the Village Head's use. Thus, this information system effectively supports the enhancement of employee accountability and serves as a vital tool for decision-making regarding the discipline and performance evaluation of village employee.